Regional Labour Markets and the Process of Unemployment - Singer, H. W. (Review of Economic Studies, 1939)
Journal Article Regional Labour Markets and the Process of Unemployment Get access H. W. Singer H. W. Singer Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 7, Issue 1, October 1939, Pages 42–58, https://doi.org/10.2307/2967595 Published: 01 October 1939